Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.26417/ejms.v3i1.p143-154
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Career Self-Efficacy on the Effect of Parental Career Behaviors on Career Exploration: A Study on School of Tourism and Hotel Management’ Students

Abstract: This study aims to investigate the impact of parental career behaviors on undergraduate student’s career exploration and the mediating role of career self-efficacy. In the literature it is suggested that some social and individual factors facilitate students’ career exploration. Therefore, parental career behaviors and career self-efficacy is considered as predictors of student’s career exploration attitudes within the scope of the study. In this respect, data which are collected from 405 undergraduate student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 6 publications
1
15
1
5
Order By: Relevance
“…Career‐related parenting practices typically include career‐related support, interference, and barriers to engagement (Dietrich & Kracke, ). Appropriate forms of and an adequate amount of career‐related support from parents (e.g., expressions of interests and concerns, encouragement, instrumental assistance, emotional backing) promote adolescents’ exploring available career options, pursuing career goals, and developing career identities (Kanten et al., ; Li & Kerpelman, ; Sawitri et al., ). In contrast, parental career‐related interference (i.e., parents’ imposing their personal ideas on children's career directions and choices) and internal or external barriers to engagement (i.e., parents’ disinterest in or attributing low importance to children's career developmental issues or parents’ strains in other life domains that may hinder their engagement in children's career development) have been shown to contribute to adolescents’ career ambivalence and/or indecision (Marcionetti & Rossier, ).…”
Section: Career‐related Parental Processes and Adolescents’ Career Dementioning
confidence: 99%
See 2 more Smart Citations
“…Career‐related parenting practices typically include career‐related support, interference, and barriers to engagement (Dietrich & Kracke, ). Appropriate forms of and an adequate amount of career‐related support from parents (e.g., expressions of interests and concerns, encouragement, instrumental assistance, emotional backing) promote adolescents’ exploring available career options, pursuing career goals, and developing career identities (Kanten et al., ; Li & Kerpelman, ; Sawitri et al., ). In contrast, parental career‐related interference (i.e., parents’ imposing their personal ideas on children's career directions and choices) and internal or external barriers to engagement (i.e., parents’ disinterest in or attributing low importance to children's career developmental issues or parents’ strains in other life domains that may hinder their engagement in children's career development) have been shown to contribute to adolescents’ career ambivalence and/or indecision (Marcionetti & Rossier, ).…”
Section: Career‐related Parental Processes and Adolescents’ Career Dementioning
confidence: 99%
“…To our knowledge, studies in this field have predominantly used variable‐centered approaches in analyses and examined the unique associations between different parental processes and child career developmental outcomes at the average level (i.e., examining the associations among variables at the entire sample level rather than further classify the entire sample into subgroups ) (e.g., Kanten et al., ; Leung et al., ; Li & Kerpelman, ; Meece et al., ; Sawitri et al., ; Sawitri et al., ; Sawitri et al., ). Although a number of important findings have been obtained from prior research, some questions cannot be addressed by utilizing variable‐centered approaches.…”
Section: Career‐related Parental Processes and Adolescents’ Career Dementioning
confidence: 99%
See 1 more Smart Citation
“…Perceived parental support, supportive parental behavior, and the parent-adolescent relationship are important sources and predictors of career decision-making self-efficacy (Garcia, Restubog, Bordia, Bordia, & Roxas, 2015), vocational identity (Tracey, Lent, Brown, Soresi, & Nota, 2006), vocational self-concept (Savickas, 2005), career interests (Turner, Steward, & Lapman, 2004), and career aspirations (Cheng & Yuen, 2011). They are also positively associated with career self-exploration (Kanten, Kanten, & Yeşiltaş, 2016), active career exploration (Noack, Kracke, Gniewosz, & Dietrich, 2010;Neuenschwander, 2008), shaping of career goals (Dietrich & Salmela-Aro, 2013), and selfconfidence and motivation to achieve goals (Ginevra, Nota, & Ferrari, 2015;Garcia, Restubog, Toledano, Tolentino, & Rafferty, 2011). In addition, many studies have found a positive relationship between parental support and career adaptability (Guan et al, 2016(Guan et al, , 2015Hirschi, 2009).…”
Section: The Importance Of Parental Support and Behaviorsmentioning
confidence: 99%
“…Siswa SMK yang masih tergolong pada kategori remaja mempunyai tugas perkembangan yang berkenaan dengan identitas karier, seperti melakukan perencanaan ataupun eksplorasi terhadap berbagai kemungkinan karier yang akan dikerjakannya (Erikson, 1963). Seorang siswa harus memulai mengeksplorasi kariernya sedini mungkin ketika mereka berada di sekolah menengah (Knight, 2015), tujuannya adalah agar ia bisa menyiapkan diri, mengetahui kemungkinan dan kesempatan serta agar dapat beradaptasi pada keadaan yang tidak terduga (Kanten et al, 2016).…”
Section: Pembahasanunclassified